2017
DOI: 10.1111/sms.12981
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for football injuries in young players aged 7 to 12 years

Abstract: Football (soccer) is very popular among children. Little is known about risk factors for football injuries in children. The aim was to analyze potential injury risk factors in 7- to 12-year-old players. We collected prospective data in Switzerland and the Czech Republic over two seasons. Coaches reported exposure of players (in hours), absence, and injury data via an Internet-based registration system. We analyzed time-to-injury data with extended Cox models accounting for correlations on team- and intra-perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 27 publications
(30 reference statements)
5
62
0
2
Order By: Relevance
“…Moreover, it has been reported that these injuries could be increased by using artificial surface in addition to inappropriate footwear (Kaumeyer & Malone, 1980;Faude et al, 2013;Rössler et al, 2018). However, the AJM assessed in the basketball, gymnastics and volleyball group resulted to be in line with the reference values reported in scientific literature (Boone & Azen, 1979;Kumar et al, 2011;Francia et al, 2019).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Moreover, it has been reported that these injuries could be increased by using artificial surface in addition to inappropriate footwear (Kaumeyer & Malone, 1980;Faude et al, 2013;Rössler et al, 2018). However, the AJM assessed in the basketball, gymnastics and volleyball group resulted to be in line with the reference values reported in scientific literature (Boone & Azen, 1979;Kumar et al, 2011;Francia et al, 2019).…”
Section: Discussionmentioning
confidence: 62%
“…Such phenomenon may be due to the gradual increase in the stiffness of foot flexor muscles in particular of triceps surae (Kaumeyer & Malone, 1980;Terada et al, 2013;Francia et al, 2018;Rössler et al, 2018). However, the real cause of a limited AJM condition in young soccer players and is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on youth football have reported no differences in injury risk between boys and girls. 5,6,42,43 We analyzed sex as a potential risk factor in the entire cohort but detected no significant associations. In addition, separate risk factor analyses were performed for boys and girls.…”
Section: Differences In Fpkpa and Injury Risk Between Boys And Girlsmentioning
confidence: 97%